Profissionalização e serviços socioassistenciais: elementos críticos para o debate da relação entre proteção social e trabalho - Biondo, Josiane (2014)
This study aims to critically reflect on the presence of professionalization to work services as a form of social assistance service. Its starting point is the assumption that labor and social protection historically maintain a conflictual relationship. In the capitalist society, the social rights guaranty presents itself subordinated to the interests of capital. The relevance of professionalization as a social assistance service was analyzed taking into account the disputes over different conceptions of social protection. Not only the author analyzed bibliographic references but also developed qualitative study using semi-structured interviews with social assistance services of professionalization managers/coordinators in São Paulo city. These services are sponsored by non-governmental organizations, thus belonging to the private field. The investigative process allowed the approximation to real and concrete movement towards totality and historicity. Among the key findings are: a) social assistance policy doesn t have the required resources and should not be responsible for professionalization to work; b) emphasis on productive inclusion follows from the primacy of a conservative and meritocratic notion of social protection; c) besides the risk of users poor integration in labor market, there is a risk to social assistance to corroborate the reproduction of an ideological discourse that understands the work as a solution to "social exclusion"